Reutericyclin producing Lactobacillus reuteri modulates development of fecal microbiota in weanling pigs - Yang, Yan; Zhao, Xin; Le, Minh Hong Ahn; Zijlstra, Ruurd; Gänzle, Michael (Frontiers in Microbiology, 2015)
Lactobacillus reuteri is used as probiotic culture in food and feed applications; however, strain specific properties of L. reuteri that mediate probiotic activity remain unknown. This study aimed to determine effects of feed fermentation with exopolysaccharide and reutericyclin producing L. reuteri on the transition of the gut microbiome of piglets after weaning. The reutericyclin and reuteran producing L. reuteri TMW1.656 was compared to the reutericyclin negative and levan producing L. reuteri LTH5794 and unfermented controls. Both strains were fermented at conditions supporting exopolysaccharide formation, or at conditions not supporting exopolysaccharide formation. Fecal microbiota were characterized by partial sequencing of 16S rRNA genes, and by quantitative PCR targeting clostridial toxins. The transition to solid food resulted in a transient increase of Proteobacteria to 12% of total bacteria, and increased bacterial diversity by increasing the abundance of anaerobic fiber fermenting Firmicutes. Three weeks after weaning, Prevotella and Lactobacillus were among the dominant bacterial genera. Feed fermentation with L. reuteri affected the abundance of few bacterial taxa and particularly reduced the abundance of Enterobacteriaceae (P < 0.05) when compared to unfermented controls. Reutericyclin producing L. reuteri increased the abundance of Dialister spp. and Mitsuokella spp. (P < 0.05) but did not influence the abundance of clostridial toxins in the feces. In conclusion, data on the contribution of specific metabolic activities of L. reuteri to probiotic activity will facilitate the strain selection for probiotic applications in food and feed.